Degradasi Zat Warna Congo Red Menggunakan Komposit TiO2 Termodifikasi Bentonit-Alginat - Paramitha, Sylvia; Riyani, Kapti; Setyaningtyas, Tien (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2024)
Congo red is a synthetic dye whose waste needs to be minimized using a photodegradation method with bentonite-alginate-modified TiO2 composite as a photocatalyst. This research aims to determine the characteristics of bentonite-alginate modified TiO2 composite and its effect as a photocatalyst in the degradation of congo red. The bentonite-alginate modified TiO2 composite has a characteristic band gap energy of 3.07 eV with TiO2 diffraction peaks in the anatase, bentonite, and semi-crystalline alginate phases with irregular sphere-like morphology. Bentonite-alginate modified TiO2 composite showed the best activity at pH 7 for 3 hours of irradiation with a TiO2-bentonite mass ratio of 2:4 which showed a degradation percentage of 38.86% in UV light and 44.95% in visible light.